Pioneering Digital Ventures: Investigating Proactive Personality, Education, and Opportunity in Malaysian Higher Education - Daisy Mui Hung Kee; Yen Jou Khor; Jie Ning Khor; Jia Yue Han; Xin Lan Jiang; Ayushi Singh (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Digital entrepreneurship has become increasingly important in the context of Industry 4.0. This study explores the connections between digital entrepreneurial intention, proactive personality, entrepreneurial education, and entrepreneurial opportunity among Malaysian public university students. Additionally, it examines the mediating roles of attitudes, subjective norms, and PBC, guided by the TPB. A quantitative research design was employed, collecting data from 250 students, which was then analyzed using SPSS to test the proposed model. The findings reveal that entrepreneurial education and PBC are significant predictors of students’ digital entrepreneurial intention. Moreover, proactive personality, entrepreneurship education, and entrepreneurial opportunity indirectly influence digital entrepreneurial intention via PBC. These results contribute to a more nuanced understanding of the factors driving digital entrepreneurial intention and highlight the importance of fostering educational environments that support entrepreneurship. The study provides valuable insights for educators and policymakers to develop strategies that enhance digital entrepreneurial capacities among students, promoting innovation and self-employment opportunities.